Privatization of Dwelling Rooms in Hostels: Problems of Nowadays - Оніщенко, Ольга Вікторівна; Козацька, Юлія Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
Formulation of the problem. Necessity of paying special attention to the privatization of dwelling rooms in the hostels is directly related to the fact that during its implementation, citizens have many problems with legal law, mainly because of a lack of legal security of normative regulation of this issue. Today, privatization of housing for the majority of Ukrainian citizens was solved, but remains unprotected groups of population that is deprived their constitutional right for housing. Therefore, you should define main problems that come up during the process of privatization. The main material research. The memoir determined that the room in the hostel according to the Law recognizes housing. It is established that privatization of these rooms is possible not in all hostels, only those which belong to public housing and which transferred to the ownership of local communities. Citizens must live in this room for at least five years this is the main condition for privatization. One of the problems associated with the privatization of living rooms is the lack of a competent body that would deal with these issues. The article noted that was not completed three-year national target program in which hostels transfer to ownership of local communities due to lack of financing from the state budget. It is note that the analysis of jurisprudence in this category of cases indicates that citizens have opportunity to privatize their housing, but it concerns not all cases. Analyzed in draft law allowed to conclude that the realization of housing rights of hostels residents is very real but needs time and financial support and unquestioningly adopting these laws. Conclusions. In the result of investigation of this problematic issue was found that way of solving it is adoption of appropriate laws which in turn requires the expenditure of time, otherwise citizens will be deprived of realize their constitutional right to housing.